2018
DOI: 10.1111/bcp.13748
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐IL‐7 receptor α monoclonal antibody (GSK2618960) in healthy subjects – a randomized, double‐blind, placebo‐controlled study

Abstract: GSK2618960 was well tolerated and blocked IL-7 receptor signalling upon full target engagement. Although there was no discernible impact on peripheral T cell subsets in healthy subjects, GSK2618960 may effectively modulate the autoinflammatory activity of pathogenic T cells in diseased tissue. A relatively short half-life is likely the result of target-mediated rather than ADA-mediated clearance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 42 publications
4
32
0
Order By: Relevance
“…The expression of IL-4, a classic marker for Th2 cells, is increased by IL-7 and is a direct cause of edema (45,46). This cytokine's activity is targeted for diseases related to pathogenic T-cells (47). Th2 cells express both CCR3 and CCR4 receptors that bind chemokines to direct their migration to the site of injury or infection (48,49).…”
Section: Discussionmentioning
confidence: 99%
“…The expression of IL-4, a classic marker for Th2 cells, is increased by IL-7 and is a direct cause of edema (45,46). This cytokine's activity is targeted for diseases related to pathogenic T-cells (47). Th2 cells express both CCR3 and CCR4 receptors that bind chemokines to direct their migration to the site of injury or infection (48,49).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, targeting IL7Rα using specific antibodies may also affect T cells 53 and lead to immunodeficiency in patients. However, a recent study showed that treating healthy subjects with anti-human IL7R antibody was well tolerated and did not result in obvious alterations in immune cell populations and inflammatory cytokine profiles 54 . Thus, treatment with anti-IL7R antibodies might provide a key therapeutic approach especially for TKI-resistant ALL once the different antibodies are characterized regarding their side-effects and compared with standard chemotherapy in appropriate clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…This represents an important drawback, as potential therapeutic benefits may be counteracted by associated off-target toxicities and severe combined immunodeficiency [ 256 ]. Nevertheless, recent studies suggest that immunosuppression induced by treatment of mouse autoimmune arthritis with an anti-IL-7Rα ADC could be well tolerated clinically for a period of time [ 257 ], and very promising results have been reported from anti-IL-7R mAb clinical trials for autoimmune diseases [ 258 ]. Overall, current information on the major contribution of normal IL-7R signaling to the onset, maintenance, and progression of acute leukemias opens a new and major area of research to develop and validate novel therapies focusing on the IL-7R pathway.…”
Section: Potential New Targets For T-all Immunotherapymentioning
confidence: 99%